2005
DOI: 10.7202/705373ar
|View full text |Cite
|
Sign up to set email alerts
|

État du développement technologique en matière d'enlèvement des métaux des effluents industriels

Abstract: Cette étude trace un profil des diverses technologies utilisées et en développement pour la séparation et/ou la récupération des métaux dans les effluents industriels. Les principes de fonctionnement de ces technologies sont abordés, ainsi que leurs avantages et limites d'utilisation. Les procédés d'enlèvement et de récupération des métaux comprennent les techniques de précipitation (formation d'hydroxydes, de carbonates, de sulfures, etc.) et coprécipitation (sels de fer et d'aluminium, etc.), d'adsorption (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 49 publications
0
23
0
4
Order By: Relevance
“…Since metals are non-biodegradable [9][10][11], and may be bioaccumulated in living tissues, their removal from wastewater is nowadays legally imposed [12]. Most technologies are available to remove metals from industrial waste including precipitation [13], ion exchange [14,15] cementation [16][17][18], electrodepositing [19], membrane separation technology [20] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since metals are non-biodegradable [9][10][11], and may be bioaccumulated in living tissues, their removal from wastewater is nowadays legally imposed [12]. Most technologies are available to remove metals from industrial waste including precipitation [13], ion exchange [14,15] cementation [16][17][18], electrodepositing [19], membrane separation technology [20] etc.…”
Section: Introductionmentioning
confidence: 99%
“…So at least half of the residue is composed of calcium sulfate when we use lime. Other authors concluded the same in the past [15,32]. Moreover, the electrolytic cell was capable of producing enough hydroxyl ions (the product of electrolysis of water at the cathode electrodes) to compensate the acid-buffer and make the soil leachates alkaline.…”
Section: Heavy Metals Removal From Aslmentioning
confidence: 84%
“…Many methods have been developed to remove heavy metals from industrial effluents [12,13], including precipitation, co-precipitation, electrodeposition, electrocoagulation, cementation, membrane separation, solvent extraction, ionexchange, adsorption and biosorption [14,15]. In spite of good extraction of metals achieved in chemical treatment (using either Ca(OH) 2 or NaOH as precipitating agent), the large consumption of chemicals implies relatively high operating cost [14,15]. Likewise, the precipitates formed are voluminous and sometimes induce high sludge production [16].…”
Section: Introductionmentioning
confidence: 99%
“…They arise either from localized urban or industrial discharges or from dispersed sources such as transport or spreading on agricultural land. Many industries are concerned by the issue of metal release [5][6][7][8]. We can mention waste incineration, fossil fuel power plants, the timber industry, wine production, the plastics industry, paper or cardboard pulp manufacturers, the glass industry, surface-finishing installations and the steel industry.…”
Section: Introductionmentioning
confidence: 99%